The Antioxidant Activity of Fresh Yam and Its Changes During Processing into Flour and Storage - Lavlinesia; Monica E.; Ulyarti (Postgraduate, University of Mataram, 2023)
This research aimed to study the antioxidant activity of several cultivars of fresh yam tubers and its flour and to determine the effect of processing and storage on antioxidant activity of yam flour. The research used Complete Random Design (CRD). This study was conducted in three stages and repeated 3 times. At first stage, antioxidant activities of three types of yam were investigated. The type of yam tuber which has the highest antioxidant activity was used for second stage. At second stage, the experiment was carried out to determine the effect of processing methods on the antioxidant activity of yam flour. The treatment which produced yam flour with the highest antioxidant activity was further used in the last stage. At last stage, the experiment was carried out to determine the effect of storage on antioxidant activity. At this stage, 3 different storage times was used (0 weeks, 4 weeks and 8 weeks). The results showed that types of yam and processing treatment gave significant effect on antioxidant activity, IC50, L*, a* and b*, and total anthocyanin of yam tuber and flour. However, processing method gave insignificant effect on value of L* of yam flour. Type of yam with the highest antioxidant activity was purple yam with antioxidant activity 96,35%, IC50 44,95 μg/ml, total anthocyanin content 351,82 mg/100g, L* 46, a* 54, and b* - 21. The processing method that produce flour with the highest antioxidant activity was steaming which produce yam flour with antioxidant activity of 83.59%, IC50 67.48 μg/ml, total anthocyanin content 136.94 mg/100g, L* 66, a* 26, and b* -15. There was a decrease in antioxidant activity, total anthocyanin content, L*, a* and b* of yam flour during storage of 4 and 8 weeks